The mixed legacy of the European Neighbourhood policy: The Moroccan exception - Dragoș-Ștefan Calcan (CES Working Papers, 2020)
Since the creation of the European Neighbourhood Policy, the EU has aimed to create a ring of stability outside its borders, in its eastern and southern neighbourhoods. In this challenging landscape, going from east to south, one of the few European successes in terms of neighbourhood policy has been Morocco, country which became a privileged partner of the EU. The paper assesses Morocco's successful cooperation with the EU, which cannot be separated from the developments regarding Western Sahara. The paper argues, by using a neo-realist approach, that the EU-Moroccan success story can be explained through the lens of history and the mutual search for security enhancement. Even though the Moroccan case study presents specific characteristics, a security centred approach could benefit the EU in relation to other neighbour countries.
Keywords: 330; EU; neighbourhood policy; Morocco; Western Sahara; security